690. Bacterial Coinfections Among Adults Hospitalized with Community-Associated Influenza, 2016–2017. (26th November 2018) - Kraushaar, Vit; Kirley, Pam Daily; Coates, Ashley; Reingold, Arthur
Abstract: Background: Influenza and bacterial coinfection are associated with increased symptom severity and worse health outcomes. We used data from the population based Influenza Hospitalization Surveillance Network (FluSurv-Net) California site to describe adult influenza hospitalizations with and without bacterial coinfections and evaluate the risk of severe disease. Methods: We included data from adults hospitalized with laboratory confirmed influenza during the 2016/2017 influenza season who resided in San Francisco, Alameda or Contra Costa counties and had a bacterial culture performed ≤ 3 days after admission. We excluded records for healthcare facility-associated influenza. Univariate analyses were used to describe demographics, clinical characteristics and outcomes. Multivariate logistic regression was used to evaluate the effect of bacterial coinfection as a risk factor for severe outcome, defined as admission to an intensive care unit (ICU) or death during hospitalization. Results: Among 2, 029 adult influenza hospitalizations, 102 had ≥1 positive bacterial cultures. There were 119 bacterial isolates from blood (58), respiratory sites (60), and joint fluid (1). The most frequent blood isolates were Streptococcus pneumoniae (11), and Staphylococcus aureus (10). The most frequent respiratory isolates were S. aureus (30) and S. pneumoniae (7). Coinfected persons were younger (median age 71 vs. 78), and more likely to have past or current alcohol abuse or immunosuppression. Coinfected patients were more likely to be admitted to an ICU (45% vs. 15%) or die (16.0% vs. 3.6%). The median length of hospital stay was twice as long for coinfected patients (6 days vs. 3). In multivariate analyses, bacterial coinfection (aOR, 4.49; 95% CI, 2.99–6.72), chronic lung disease (aOR, 1.52; 95% CI, 1.18–1.95) and cardiovascular disease (aOR, 1.48; 95% CI, 1.15–1.90) were associated with a severe outcome. Conclusion: Bacterial coinfection was associated with a four-fold higher risk of ICU admission and death during hospitalization. This study highlights the need for clinicians to maintain a high index of suspicion for the presence of bacterial coinfection among patients with influenza requiring hospitalization. Disclosures: All authors: No reported disclosures.